Penerapan Metode Student Teams Achievement Division (STAD) untuk Meningkatkan Hasil Belajar Bahasa Inggris - Lily Lily; Widya Nisa (JURNAL RISET RUMPUN ILMU PENDIDIKAN, 2025)
This study aimed to improve the English learning outcomes of 9B grade students at UPT SMP Negeri 28 Medan in the 2024/2025 academic year through the implementation of the Student Teams Achievement Division (STAD) method. This research applied a Classroom Action Research (CAR) approach conducted in two cycles. Data were collected through learning outcome tests administered in the pre-cycle, Cycle I, and Cycle II. The results showed that the STAD method improved students’ average scores from 67.125 in the pre-cycle to 73.75 in Cycle I, and further to 78.81 in Cycle II. The percentage of students achieving the Minimum Mastery Criteria (KKM) increased from 25% to 78.1%. The Wilcoxon test indicated a statistically significant difference in learning outcomes before and after the intervention. The findings suggest that the STAD method is an effective cooperative learning strategy to enhance students’ English performance and foster collaborative classroom skills. Nevertheless, teachers must consider individual differences within teams to ensure equitable learning experiences for all students.